Effects of prenatal micronutrients supplementation timing on pregnancy‐induced hypertension: Secondary analysis of a double‐blind randomized controlled trial - Yingying Liu; Nan Li; Zuguo Mei; Zhiwen Li; Rongwei Ye; Le Zhang; Hongtian Li; Yali Zhang; Jian‐meng Liu; Mary K. Serdula (Wiley, 2021)
Abstract In this secondary analysis of data from a double‐blind randomized controlled trial (clinicaltrials.gov identifier: NCT00133744) of micronutrient supplementation (multiple micronutrients [MMN], iron-folic acid [IFA] and folic acid [FA] alone), we examined the potential modifying effect of gestational age at enrolment on the association of antenatal supplementation and pregnancy‐induced hypertension (PIH). We included 18,775 nulliparous pregnant women with mild or no anaemia who were enrolled at 20 weeks of gestation or earlier from five counties of northern China. Women were randomly assigned to receive daily FA, IFA or MMN from enrolment until delivery. We used logistic regression to evaluate the association between PIH and timing of micronutrient supplementation. The incidence of PIH was statistically significantly lower among women who began MMN supplementation before 12 gestational weeks compared with women who began MMN supplementation at 12 weeks or later (RR = 0.74, 95% CI: 0.60-0.91). A similar protective effect was observed for both early‐onset (<28 weeks, RR 0.45, 0.21-0.96) and late‐onset of PIH (≥28 weeks, RR 0.77, 0.63-0.96). No statistically significant association was observed between PIH occurrence and timing of supplementation for FA or IFA. Maternal MMN supplementation and antenatal enrolment during the first trimester of pregnancy appeared to be of importance in preventing both early‐ and late‐onset of PIH.